Memetakan Sebaran Lanskap Budaya pada Situs Kesultanan Serdang dan Situs Kerajaan Bedagai di Kabupaten Serdang Bedagai: Memetaan Perubahan Lanskap dan Sebaran Objek Lanskap Budaya pada Situs Kesultanan Serdang dan Situs Kerajaan Bedagai di Kabupaten Serdang Bedagai, Provinsi Sumatera Utara - Saputra, Dedi; Nurhayati, Nurhayati; Arifin, Hadi Susilo (Berkala Arkeologi, 2025)
Serdang Bedagai Regency was formerly the territory of the Serdang Sultanate, the Bedagai Kingdom, Padang, and Bajalinggei. Numerous historical landscape remains dating back more than 50 years have been identified in the form of objects, buildings, structures, and sites. Several challenges remain, including limited identication, dokumentation, and maintenance effort, as well as issues related to population growth, land conversion, land conflicts, and zoning regulations. The main objective of this study is to map landscape changes and the distribution of cultural landscape objects inherited by the Serdang Sultanate Site and the Bedagai Kingdom Site. The method used is qualitative and spatial descriptive analysis with a Landscape Character Assessment approach. As a result, The findings reveal that Sergai Regency prossesses two Regency-level Cultural Heritage Sites. A total of 50 registered objects and 29 New Discoveries. The results of the map delineation indicate that significant landscape changes have occurred. Factors influencing landscape changes are the social revolution of 1946, the absence of zoning and a preservation agenda, minimal budget, land conversion, land conflicts, and the rate of population growth. The Serdang Palace Complex has been converted into housing and there are 16 new object discoveries, while at the Bedagai Kingdom Site there are two Kingdom site locations with 6 newly discovered object.